(untitled) (The South Asianist Journal, 2014)
’When we think of wars in our times, our minds automatically turn to Iraq and Afghanistan, but the bigger war is the on-going war against the earth’. Thus begins Vandana Shiva’s alarming exposé of what she believes is an all-out capitalistic assault on Mother Earth. Here, ’[t]he global corporate economy based on the idea of limitless growth’ is presented as a ’a permanent war economy against the planet and people’—comprising a combination of ’land-grab,’ ’water wars,’ ’climate wars,’ ’forest wars,’ and ’seed wars.’